A clinical and electron microscopic study of a calcifying epithelial odontogenic tumour. Issue 2 (March 1971) - Mainwaring, A. R.; Ahmed, Ali; Hopkinson, J. M.; Anderson, P.
Abstract : The clinical features and the histological and ultrastructural appearances of a case of calcifying epithelial odontogenic tumour are described. The ultrastructural features of the cells of this tumour are comparable to cells of the stratum intermedium of the enamel organ. It is suggested that the amyloid-staining material found in this tumour is a cellular secretion rather than a cytoplasmic degeneration.